Identification of ALK, ROS1, and RET Fusions by a Multiplexed mRNA-Based Assay in Formalin-Fixed, Paraffin-Embedded Samples from Advanced Non–Small-Cell Lung Cancer Patients. (6th January 2020) - Reguart, Noemí; Teixidó, Cristina; Giménez-Capitán, Ana; Paré, Laia; Galván, Patricia; Viteri, Santiago; Rodríguez, Sonia; Peg, Vicente; Aldeguer, Erika; Viñolas, Nuria; Remon, Jordi; Karachaliou, Niki; et al.
Abstract: BACKGROUND: Anaplastic lymphoma receptor tyrosine kinase ( ALK ), ROS proto-oncogene 1, receptor tyrosine kinase ( ROS1 ), and ret proto-oncogene ( RET ) fusions are present in 5%–7% of patients with advanced non–small-cell lung cancer (NSCLC); their accurate identification is critical to guide targeted therapies. FISH and immunohistochemistry (IHC) are considered the gold standards to determine gene fusions, but they have limitations. The nCounter platform is a potentially useful genomic tool for multiplexed detection of gene fusions, but has not been validated in the clinical setting. METHODS: Formalin-fixed, paraffin embedded (FFPE) samples from 108 patients with advanced NSCLC were analyzed with an nCounter-based assay and the results compared with FISH, IHC, and reverse transcription PCR (RT-PCR). Data on response to fusion kinase inhibitors was retrospectively collected in a subset of 29 patients. RESULTS: Of 108 FFPE samples, 98 were successfully analyzed by nCounter (91%), which identified 55 fusion-positive cases (32 ALK, 21 ROS1, and 2 RET ). nCounter results were highly concordant with IHC for ALK (98.5%, CI = 91.8–99.7), while 11 discrepancies were found compared with FISH (87.5% concordance, CI = 79.0–92.9). For ROS1, nCounter showed similar agreement with IHC and FISH (87.2% and 85.9%), but a substantial number of samples were positive only by 1 or 2 techniques. Of the 25 patients deriving clinical benefit from fusion kinase inhibitors, 24 were positive by nCounter and 22 by FISH. CONCLUSIONS: nCounter compares favorably with IHC and FISH and can be used for identifying patients with advanced NSCLC positive for ALK / ROS1 / RET fusion genes.